Errors That Can Be Tolerated in Criminal Court Decisions Using A Doctrinal Approach Harmless Error in Order to Carry Out The Principles of Justice - Susilo, Erwin; Negara, Dharma Setiawan (JURNAL AKTA, 2025)
A fair criminal trial is a fundamental pillar of the justice system, ensuring that substantive justice prevails over mere procedural correctness. This article explores the essential elements of criminal verdicts, particularly legal considerations and judicial rulings, as outlined in Article 197 of the Indonesian Criminal Procedure Code (KUHAP). It further analyzes judicial errors through the doctrinal approach of harmless error. In judicial practice, errors in a judge's decision can be categorized into substantial (harmful error) and non-substantial (harmless error). Substantial errors directly affect the defendant’s rights or compromise the integrity of the trial, potentially leading to a miscarriage of justice. In contrast, non-substantial errors are procedural or administrative in nature, meaning they do not significantly impact substantive justice or alter the final outcome of the case. The harmless error doctrine, originating from common law jurisdictions, has been adopted in various legal systems, including Indonesia, to balance trial efficiency with the pursuit of material truth. This doctrine prevents the unnecessary annulment of verdicts due to minor, non-prejudicial errors that do not affect the essence of justice. By recognizing the distinction between procedural irregularities and substantive violations, courts can uphold fair trials while minimizing delays caused by technical challenges. This research underscores the necessity of a criminal justice system that is simple, swift, and cost-effective, in line with the principles of justice in Indonesia. An efficient legal framework that embraces the harmless error doctrine ensures that the judicial process remains fair without being unnecessarily rigid. Ultimately, the legal system must remain justice-oriented, prioritizing substantive fairness over procedural perfection to uphold the rule of law and protect individual rights.